Pathogens strongly associated with periodontitis. An analysis of their virulence - Lázaro Sarduy Bermúdez; Felisa Veitia Cabarrocas; Marysol Rodríguez Felipe (Medisur)
Periodontal pathogens play an important role in the periodontitis appearance and development. This is due to their interaction with the host, which leads to the destruction of the tooth insertion tissues. Virulence is defined as the mechanisms through which microorganisms are capable of producing the disease. The present bibliographic review aims to analyze the different virulence factors of pathogens strongly associated with periodontitis. In addition, reference is made to other putative species involved in the etiopathogenesis of the disease. Between July and October 2024, a bibliographic search was carried out in textbooks and periodical publications on the subject. 23 scientific articles were selected to form the body of the bibliographic review. Pathogens considered to be strongly associated with periodontitis (Aggregatibacter actinomycetemcomitans, Porphyromona gingivalis, Tannerella forsythia) possess virulence factors such as: adherence; evasion, neutralization and reduction of the host's defensive mechanisms; direct damage to tissues; induction of bone resorption and indirect tissue damage. These justify their role in the establishment, progression and destruction caused by periodontitis. Other putative species are described, such as Filifactor alocis, Desulfobulbus oralis and TM7 spp that can enhance the action of the microorganisms mentioned above; or with their own virulence, contribute to the disease development.